Population, Basking and Hatching Success of Gavialis gangeticus in Narayani River, Chitwan National Park, Nepal - Rajbhandari, Sunil Lal; Acharya, Paras Mani (Journal of Natural History Museum, 2015)
This study was carried out to investigate the habitats and abundance of the Gharials in Narayani river of Chitwan National Park from 2012 to 2013. A total of 38 Gharials including 3 hatchlings, 8 juveniles, 12 sub-adults and 15 adults were recorded during the study period. Only one breeding male was observed reflecting the critical condition for the breeding in the wild within Chitwan National Park. The abundance of the gharial was restricted in 2 areas, namely Khoria muhan and Velaunji due to suitability of the habitat conditions and minimum human disturbances. The Basking activities in relation to depth showed that > 80 % of the Gharials selected sandy banks. Among the 2 populations, the gharials in Khoria muhan preferred shallow to moderate depth of water because of presence of braided channels in the area. In contrast, the Gharials in Velaunji select deep water course of the main channel. The park management must adopt conservation measures such as ban of fishing and regular monitoring of habitats and population to maintain long term conservation of gharials in Narayani river. J. Nat. Hist. Mus. Vol. 27, 2013: 1-11